Impact of Interleukin 10 Deficiency on Intestinal Epithelium Responses to Inflammatory Signals - Papoutsopoulou, Stamatia; Pollock, Liam; Walker, Catherine; Tench, William; Samad, Sakim Shakh; Bergey, François; Lenzi, Luca; Sheibani-Tezerji, Raheleh; Rosenstiel, Phillip; Alam, Mohammad Tauqeer; Martins Dos Santos, Vitor A. P.; Müller, Werner; et al. (Frontiers in Immunology, 2021)
Interleukin 10 (IL-10) is a pleiotropic, anti-inflammatory cytokine that has a major protective role in the intestine. Although its production by cells of the innate and adaptive immune system has been extensively studied, its intrinsic role in intestinal epithelial cells is poorly understood. In this study, we utilised both ATAC sequencing and RNA sequencing to define the transcriptional response of murine enteroids to tumour necrosis factor (TNF). We identified that the key early phase drivers of the transcriptional response to TNF within intestinal epithelium were NFκB transcription factor dependent. Using wild-type and Il10−/− enteroid cultures, we showed an intrinsic, intestinal epithelium specific effect of IL-10 deficiency on TNF-induced gene transcription, with significant downregulation of identified NFκB target genes Tnf, Ccl20, and Cxcl10, and delayed overexpression of NFκB inhibitor encoding genes, Nfkbia and Tnfaip3. IL-10 deficiency, or immunoblockade of IL-10 receptor, impacted on TNF-induced endogenous NFκB activity and downstream NFκB target gene transcription. Intestinal epithelium-derived IL-10 appears to play a crucial role as a positive regulator of the canonical NFκB pathway, contributing to maintenance of intestinal homeostasis. This is particularly important in the context of an inflammatory environment and highlights the potential for future tissue-targeted IL-10 therapeutic intervention.